Details on the Pillars of the Mukhamandapa - Temples of India Project Team (Jio Institute, 2024)
The top portion of the pillars of the mukhamandapa (front porch) shows couples engaged in different activities such as love-making, dancing, and tender gestures such as a male figure removing a thorn from his partner’s foot and kissing. On the proper right pillar of the mukhamandapa, one panel shows a couple carrying weapons and embracing each other. The couple is flanked by beautiful female figures holding garlands and scarves.